2005
DOI: 10.1007/s11661-005-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spraying conditions on microstructures of Al-SiC p composites by plasma spraying

Abstract: Air plasma spraying was used to produce Al-SiC p composites as electronic packaging material. Ballmilled Al with 55 and 75 vol. pct SiC powders was repeatedly deposited onto a graphite substrate, and then mechanically removed to get free-standing 100 ϫ 100 mm composite plates of about 2-mm thickness. Different input electrical powers were employed at two spray distances of 100 and 120 mm. The SiC volume fraction and porosity in the sprayed composites were found to be dependent on spray conditions, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Thus, it is difficult for the solid Al 2 O 3 particles to be deposited on the substrate, resulting in a certain amount of loss. Similar results have also been reported by other researches . Besides, there was no other phase formed during plasma spraying, including Cr 2 O 3 , can be found.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, it is difficult for the solid Al 2 O 3 particles to be deposited on the substrate, resulting in a certain amount of loss. Similar results have also been reported by other researches . Besides, there was no other phase formed during plasma spraying, including Cr 2 O 3 , can be found.…”
Section: Resultssupporting
confidence: 91%
“…Similar results have also been reported by other researches. 20 Besides, there was no other phase formed during plasma spraying, including Cr 2 O 3 , can be found.…”
Section: Spray Distance MM 100mentioning
confidence: 97%
“…A previous study demonstrated that the Si phase in the composites resulted from the decomposition of SiC particle in the feedstock at high temperature of plasma flame. 20 Based on OM image analysis, 2-5% porosity existed in the as sprayed composites, and Al-75SiC composites contained higher porosity. The arrows in Fig.…”
Section: Microstructure Of Sprayed Compositesmentioning
confidence: 96%
“…In surface engineering field, surface MMCs have been synthesized through various methods like plasma spraying [9], cold spraying [10], laser melting [11][12][13][14], cast sinter [15][16] and electron beam irradiation method [17] etc. These fabrication techniques have many disadvantages such as particle agglomeration, formation of detrimental phases and interfacial reactions because of processing above melting point temperatures of respective metal alloys.…”
Section: Introductionmentioning
confidence: 99%